Optimalisasi Pemasaran Digital UMKM Desa Munjul melalui Penguatan Koperasi Merah Putih sebagai Strategi Ekonomi Lokal Berkelanjutan - Syofyan, Syofriza; Pratiwi, Reno; Fadhilah, Arief; Erza, Osni; Novianto, Riski Pratama; Abdilah, Obinata Ridho (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service (PkM) activity aims to enhance the digital marketing capacity of Micro, Small, and Medium Enterprises (MSMEs) in Munjul Village, Ciambar District, Sukabumi Regency through strengthening the role of the Koperasi Merah Putih. Munjul Village has local economic potential based on cassava-based products; however, the utilization of digital technology for marketing remains limited. The implementation methods included field surveys, digital literacy training, assistance in creating social media and marketplace accounts, and institutional strengthening of the cooperative as an integrated digital marketing center. The results indicate an improvement in participants’ knowledge and skills in digital marketing, the establishment of business social media accounts, and the ability to create simple promotional content. Approximately 80% of participants understood the benefits of social media in increasing sales and the cooperative’s role in collective promotion, while 90% stated that the program was beneficial for strengthening sustainable local economic development. Overall, the evaluation shows increased knowledge, understanding, and skills in cooperative-based digital marketing toward a sustainable village economy.